2022
DOI: 10.1039/d1nj06109g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and exploration of configurational dynamics in equilibratingE/Z2-aryliminothiazolidin-4-ones using NMR and estimation of thermodynamic parameters

Abstract: In the present manuscript, 2-aryliminothiazolidin-4-ones (3 and 5) were utilized as dynamic chemical systems, whose different states are modulated in a reversible fashion through specific chemical stimuli. The in-depth NMR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is industrially produced by inducing a chemically similar substance like ammonium thiocyanate (NH 4 SCN) to undergo rearrangement. 11 It can also be produced by the reaction between hydrogen sulfide and calcium cyanamide (CaCN) in the presence of carbon dioxide (CO 2 ). 12 Despite the poisonous characteristics of thiourea, its derivatives prove to be useful in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is industrially produced by inducing a chemically similar substance like ammonium thiocyanate (NH 4 SCN) to undergo rearrangement. 11 It can also be produced by the reaction between hydrogen sulfide and calcium cyanamide (CaCN) in the presence of carbon dioxide (CO 2 ). 12 Despite the poisonous characteristics of thiourea, its derivatives prove to be useful in drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…However, thiourea tends to form colorless crystals at the temperature of 182 °C (860 °F). It is industrially produced by inducing a chemically similar substance like ammonium thiocyanate (NH 4 SCN) to undergo rearrangement . It can also be produced by the reaction between hydrogen sulfide and calcium cyanamide (CaCN) in the presence of carbon dioxide (CO 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigation, we observed that 2-aryliminothiazolidinone derivatives exhibited dynamic behaviour and computed the kinetic and thermodynamic parameters of the dynamic chemical system with the help of the combined use of the coalescence temperature method and extensive peak shape analysis 44 (Fig. 2).…”
Section: Data Setmentioning
confidence: 99%
“…The experimental data of Δ G ‡ for the dynamic system was obtained from our previous investigation (Fig. 1) 44 and constitutes the endpoint for the development of CORAL QSGFEAR models. The predictive potential of the developed model is estimated with the correlation intensity index (CII), a new criterion to improve the predictive reliability of the developed model.…”
Section: Introductionmentioning
confidence: 99%